Uma história do teorema de pitágoras: demonstrações e curiosidades. - AMARAL, Jairo Sena do (2025)
This undergraduate thesis conducts a comprehensive theoretical review on the Pythagorean theorem, exploring various demonstrations of this essential mathematical equation. Furthermore, it aims to emphasize the significance of this theorem in fields such as mathematics, physics, and engineering, showcasing its applicability in different contexts. Another objective of this research is to present the history and origins of the Pythagorean theorem. This includes not only an analysis of the available knowledge about the philosopher Pythagoras but also an investigation into evidence of the use of this theorem by civilizations that existed even before the period in which Pythagoras lived. By delving into these aspects in depth, we hope to contribute to a more comprehensive and detailed understanding of the Pythagorean theorem, its foundations, and its implications in various areas of knowledge. In doing so, we seek to enrich the study of this classical theorem and foster a broader appreciation of its historical and contemporary significance.